2010
DOI: 10.1105/tpc.110.075317
|View full text |Cite
|
Sign up to set email alerts
|

Gravitropism ofArabidopsis thalianaRoots Requires the Polarization of PIN2 toward the Root Tip in Meristematic Cortical Cells  

Abstract: In the root, the transport of auxin from the tip to the elongation zone, referred to here as shootward, governs gravitropic bending. Shootward polar auxin transport, and hence gravitropism, depends on the polar deployment of the PIN-FORMED auxin efflux carrier PIN2. In Arabidopsis thaliana, PIN2 has the expected shootward localization in epidermis and lateral root cap; however, this carrier is localized toward the root tip (rootward) in cortical cells of the meristem, a deployment whose function is enigmatic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 53 publications
(94 reference statements)
10
135
0
Order By: Relevance
“…PIN2 shows either apolar or apical localization in the neighboring cortical cells, consistent with a possible defect of backward auxin recycling from the cortex to the root tip. The effect of crk5-1 mutation thus appears to be very similar to the consequence of treating roots with low concentrations of BFA, which stimulates basal-to-apical relocation of PIN2 in the cortex inhibiting root gravitropic response (Rahman et al, 2010). In fact, we observed that the crk5-1 mutation not only reduces the amount of PM-associated PIN2 in the epidermis of transition zone, but also markedly accelerates brefeldin-sensitive internalization of PIN2 in epidermal cells.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…PIN2 shows either apolar or apical localization in the neighboring cortical cells, consistent with a possible defect of backward auxin recycling from the cortex to the root tip. The effect of crk5-1 mutation thus appears to be very similar to the consequence of treating roots with low concentrations of BFA, which stimulates basal-to-apical relocation of PIN2 in the cortex inhibiting root gravitropic response (Rahman et al, 2010). In fact, we observed that the crk5-1 mutation not only reduces the amount of PM-associated PIN2 in the epidermis of transition zone, but also markedly accelerates brefeldin-sensitive internalization of PIN2 in epidermal cells.…”
Section: Discussionsupporting
confidence: 53%
“…Upwards of the crk5-1 transition zone, PIN2 was detected, if at all, as weak internalized signal in the epidermis, and its localization was shifted to apical in the cortex. Since such apical localization of PIN2 in the cortex induced by low concentration BFA treatment was previously demonstrated to abolish root gravitropic responses (Rahman et al, 2010), these data suggested that aberrant polar localization of PIN2 in both epidermis and cortex was likely responsible for the delayed gravitropic response of crk5-1 mutant roots.…”
Section: Localization Of Pins and Aux1 In The Crk5-1 Mutantmentioning
confidence: 82%
See 1 more Smart Citation
“…Newly synthesized nonpolar PIN1 and PIN2 in the cortex relocalize themselves toward the rootward domain of the plasma membrane through ADP ribosylation factor GTP-exchanging factors, such as GNOM, and the phosphorylation status of the proteins, which is regulated by the counterbalancing activities of PINOID Kinase and protein phosphatase 2A (Geldner et al, 2001;Michniewicz et al, 2007;Sukumar et al, 2009;Rahman et al, 2010). However, polarization of PIN2 in epidermal and lateral root cap cells is independent of this pathway (Rahman et al, 2010). Recycling and intracellular trafficking of PIN2 require the retromer proteins SNX1 and VACUOLAR PROTEIN SORTING29 (VPS29) (Jaillais et al, 2006(Jaillais et al, , 2007.…”
Section: Snx1-dependent Endosomal Pathway Regulates Intracellular Auxmentioning
confidence: 99%
“…This is of particular interest as a recent experimental study (Rahman et al 2010) (focussing on the meristem) suggests that changing the direction of the cortical cells' efflux carriers significantly alters the auxin distribution and gravitropic response. It is straightforward to see how changing the location of these efflux carriers affects the analytical results: in the single-layer analysis, the effective velocity in the cortex becomes v cor = B 3 P P I N /2, and we accordingly use this formula for v cor in place of (3.26e) when evaluating the dynamics of the three-layer model, (3.32) with (3.14d-j).…”
Section: Biological Predictionsmentioning
confidence: 99%